Design your own anime and manga characters : step-by-step lessons for creating and drawing unique characters : learn anatomy, poses, expressions, costumes, and more - Choi, T. B. (Rockport Publishers, 2022)
For beginner to intermediate artists, Design Your Own Anime and Manga Characters demonstrates how to conceive and draw original characters for these popular art/entertainment genres.